Perlawanan LSM Terhadap PT Indorayon - Mochtar Haboddin (Jurnal Ilmu Sosial dan Ilmu Politik, 2008)
This paper discusses the struggle of environmental NGO in protecting the environment. Through the case of PT Indorayon paper pulp and rayon fiber plant in North Sumatra, this paper highlights a new approach of NGO's strategy in protecting environment from industrial exploitation. By combining traditional approach such as protest and demostration with formal and legal channel as well as network among NGOs, the movement has successfully forced PT Indorayon to close down. This paper suggests that the case of NGOs movement against PT Indorayon, could becomea model of social movement in Indonesia, particularly in environmental issues.